Adolescent Homelessness: A Roundtable Discussion - Staff, Editorial (Maine Policy Review, 1999)
Where do homeless adolescents come from? Are there more homeless youth today than ten years ago? How do we help these youth? What do they need? In December 1998, these questions formed the core of a Maine Policy Review roundtable discussion featuring: State Representative Michael Quint; Dana Totman, deputy director of the Maine State Housing Authority; Christine O’Leary, coordinator of Portland’s Preble Street Resource Teen Center; Bob Rowe, executive director of New Beginnings in Lewiston; and Brad Coffey, chair of the board of Bangor’s Shaw House from 1994-1998. In their wide-ranging discussion, the participants focused on the varied circumstances that lead to adolescent homelessness, the need for expanded low-barrier services to help these youth, and the need for some state entity to be responsible for and responsive to the unique needs of homeless adolescents. However, the participants caution that when designing policy solutions, it is important to involve adolescents. Furthermore, it is vital that everybody understand this problem because at its core, adolescent homelessness is a community problem that requires state and local investment. At risk, the participants note, is the vitality of Maine’s most important future resource—its young people.